Strategi Penyelesaian Pajak Pertambahan Nilai Dalam Kasus Lebih Bayar - Nisa, Khoirun; Safira, Selma Putri (Media Akuntansi Perpajakan, 2025)
The purpose of this research is to study various ways to settle Value Added Tax (VAT) in cases of overpayment by PT XYZ. Overpayment of VAT often occurs for Taxable Entrepreneurs (PKP) when input tax exceeds output tax in a tax period. PKP can choose restitution or compensation in this case. This research uses qualitative methodology and case study. Data were obtained through interviews with internal parties, documentation of PT XYZ's 2023 VAT Period Tax Returns, and literature review. The research results show that PT XYZ consistently uses a compensation strategy for excess VAT payments because it is more administratively efficient, does not require an audit process, and provides time certainty. This strategy has proven effective in managing tax obligations without incurring tax penalties. The results indicate that the application of the overpayment settlement method should be adjusted to liquidity conditions, business needs, and potential administrative risks